Desempenho agronômico e diagnose foliar da aveia preta em função da calagem em plantio direto - Silva, Tiago Roque Benetoli (2012)
The soil acidity in no tillage system could be resolved by lime superficial application, improvement to crop mineral nutrition and yield. The experiment carried out on a Rhodic Kandiudalf in Botucatu, São Paulo State, Brazil, in dry conditions, aiming to evaluate the agronomic development and leaf diagnosis of black oat plants, under superficial liming in no tillage system. A randomized complete block design was used, with four replications, the treatments were superficial application of different dolomítico lime rates (R0 = zero – without lime; R1 = 1,8 t ha-1 – lime to increase the base saturation at 50%; R2 = 3,6 t ha-1 – lime to increase the base saturation at 70% and R3 = 5,4 t ha-1 – lime to increase the base saturation at 90%), in October 2002. The black oat Common cultivar was seed in April 2004, in to second year, after the crop rotation of millet (spring) – common bean (summer) – black oat (autumn-winter). The results showed that: the black oat had yield increase by superficial liming, mainly to most dry matter and grain per panicule. Beyond, the superficial liming application did not prejudice leaf diagnosis of culture.